“Menino matuto não sei”: a trajetória do ser brincante no processo criativo da cena junina - Espirito Santo, Walisson Bispo do (2022)
In studies of popular culture and contemporary’s creative processes, there are no studies that promote connection between the artistic and cultural manifestation of the June country dance, autobiographical issues, corporal conscience and theatrical aspects. In view of this, I elaborate, in this research, a scenic experiment based on my personal, artistic and professional experiences in the June country dance. The general objective is to investigate the senses produced in the scenic of June construction with my body, the result of my trajectory as a player in the interstice 2003-2020. I choose the (Auto)biographical Method (JOSSO, 2014; CHIZZOTTI, 2008), since this is a qualitative and descriptive-interpretative study (MARCONI; LAKATOS, 2017; PRODANOV; FREITAS, 2013), to direct the creative process under the perspective of Klauss Vianna's Technique (VIANNA, 1990; MILLER, 2007). Therefore, I use two perspectives: theoretical and practical/creative. The first is a contextualization about the June country dance (GIFFONI, 1955; 1964; CAMINADA, 1999; CHIANCA, 1999; LEAL, 2004), creative process (OSTROWER, 2014), theatricality (FERNANDES, 2013; FÉRAL, 2015) and body awareness (QUEIROZ, 2012). The second approach includes the stages of the creative process: inaction, “waking up” of the body, activities of (self)conscience and awareness, recollections, elaboration of the scenic text, cenocentric memorization, rehearsals and data generation. Thus, the analytical procedures used involve: i) the description of the types of language that constitute the scene of June; ii) the description of spatiality, clothing and lighting; iii) the description of the scene based on the playful, vector and creative processes of the Technique; iv) the interpretation of the scene based on the Technique and the subjective creative process; v) the expansion of interpretation based on the notion of autobiographical method. In the intersection of the roles of producer, actor, dancer, character, spectator and analyst, I produce different meanings about the scenic of June experiment, which are anchored to my life experiences, creating a “significant polyphony” (FERNANDES, 2013) between art, science and life. In this sense, this research methodologically contributes to the study of artistic creative processes in general.